2020
DOI: 10.1111/1748-5967.12434
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical analysis and pathogenicity of entomopathogenic fungi to Diaphorina citri Kuwayama (Hemiptera: Liviidae)

Abstract: Asiatic citrus psylla, Diaphorina citri, Kuwayama (Hemiptera: Liviidae) is an economic pest of citrus groves and a vector of the bacterium, Candidatus Liberibacter spp., one of the causative agents of citrus greening. In order to estimate the infectivity of six different isolates of Beauveria bassiana, Metarhizium anisopliae and Isaria fumosorosea, fungal bioassay was performed on the adults of D. citri. Adults of D. citri were treated individually with 1 × 10 5 , 1 × 10 6 , 1 × 10 7 , 1 × 10 8 , 2 × 10 8 spor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Currently, more than 1,000 species of EPF have been reported, including commercially applied Metarhizium anisopliae , Beauveria bassiana , Isaria fumosorosea, and Metarhizium rileyi ( Kim Jae et al, 2013 ; Grijalba Erika et al, 2018 ; Jiang et al, 2019 ; Malinga Lawrence and Mark, 2021 ; Wang et al, 2021 ; Acharya et al, 2022 ; Faria et al, 2022 ; Im et al, 2022 ), as well as literature reported Paecilomyces var iotii , Hirsutella citriformis , and Akanthomyces lecanii ( Gandarilla-Pacheco et al, 2013 ; Cortez-Madrigal et al, 2014 ; Hussain et al, 2018 ; Naeem et al, 2020 ). However, the resources of EPF are insufficient due to their host specificity, which could affect their commercial production and application ( Wichadakul et al, 2015 ; Zhang et al, 2020 ; Islam et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, more than 1,000 species of EPF have been reported, including commercially applied Metarhizium anisopliae , Beauveria bassiana , Isaria fumosorosea, and Metarhizium rileyi ( Kim Jae et al, 2013 ; Grijalba Erika et al, 2018 ; Jiang et al, 2019 ; Malinga Lawrence and Mark, 2021 ; Wang et al, 2021 ; Acharya et al, 2022 ; Faria et al, 2022 ; Im et al, 2022 ), as well as literature reported Paecilomyces var iotii , Hirsutella citriformis , and Akanthomyces lecanii ( Gandarilla-Pacheco et al, 2013 ; Cortez-Madrigal et al, 2014 ; Hussain et al, 2018 ; Naeem et al, 2020 ). However, the resources of EPF are insufficient due to their host specificity, which could affect their commercial production and application ( Wichadakul et al, 2015 ; Zhang et al, 2020 ; Islam et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20][21] To overcome these problems, an eco-friendly and long-lasting control strategy, for example entomopathogenic fungi (EPF), is the basic need of time. 22 EPF are cosmopolitan and effective biocontrol agents with no adverse effects on the environment. 23 In the past, different species of EPF have been reported as effective biocontrol agents for various insect pests, [24][25][26][27][28][29][30] including O. hyalinipennis.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, O. hyalinipennis has developed resistance to major insecticide groups, such as pyrethroids, organophosphates, spinosyns, avermectins, pyrroles, neonicotinoids and insect growth regulators 16–21 . To overcome these problems, an eco‐friendly and long‐lasting control strategy, for example entomopathogenic fungi (EPF), is the basic need of time 22 . EPF are cosmopolitan and effective biocontrol agents with no adverse effects on the environment 23 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a large number of entomopathogenic fungi have been reported for the control of D. citri. Paecilomyces variotii, Hirsutella citriformis and Akanthomyces lecanii have the ability to infect D. citri [27][28][29][30]. In addition, B. bassiana and M. anisopliae, which have been commercially produced and applied, can also be used for the control of D. citri.…”
Section: Introductionmentioning
confidence: 99%